Using preferred fluids and different reward schedules to motivate rhesus macaques (Macaca mulatta) in cognitive tasks. (August 2019) - Gray, Helen; Thiele, Alexander; Rowe, Candy
Rhesus macaques ( Macaca mulatta ) used in behavioural neuroscience are often required to complete cognitively complex tasks, for which a high level of motivation is essential. To induce motivation, researchers may implement fluid-restriction protocols, whereby freely available water is limited, such that fluid can be used as a reward in the laboratory. A variety of different rewards and schedules are used, but there exists a lack of data assessing their effectiveness. In this study, we aimed to quantify fluid preference in rhesus macaques and to use these preferences to compare the motivational quality of different reward schedules: the monkey's previous reward (i.e. the fluid used to reward them in past studies), their new preferred reward, a variable schedule of previous and preferred reward, and a choice between the previous and preferred rewards. We found that it may be possible to reduce the level of restriction if an adequately motivating preferred reward is identified, but that this is dependent on the animal. Each monkey responded differently to both the fluid-preference assessments and to the different reward schedules. As such, monkeys should not be subject to 'blanket' protocols but should be assessed individually to maintain adequate scientific data collection at the least severe level of fluid restriction.